2017
DOI: 10.1155/2017/7379693
|View full text |Cite
|
Sign up to set email alerts
|

In VitroPlant Regeneration from Commercial Cultivars of Soybean

Abstract: Soybean, a major legume crop, is the source of vegetable oil and protein. There is a need for transgenic approaches to breeding superior soybean varieties to meet future climate challenges. Efficient plant regeneration is a prerequisite for successful application of genetic transformation technology. Soybean cultivars are classified into different maturity groups based on photoperiod requirements. In this study, nine soybean varieties belonging to different maturity group were regenerated successfully from thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 35 publications
4
28
0
8
Order By: Relevance
“…We found that, 1 2 M519 media fortified with KT 4.0 mg L −1 + NAA 0.1 mg L −1 showed maximum of 80% shoot regeneration frequency by using HCN explants, while all other combinations also induced shoot formation, albeit with a reduced percentage. Additionally, explant types (HCN, TCN, and WCN) exhibited different responses to different combinations of plant hormones (KT, NAA, and 6-BA), suggesting that, regeneration ability of plant depends on explant type and age [22,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that, 1 2 M519 media fortified with KT 4.0 mg L −1 + NAA 0.1 mg L −1 showed maximum of 80% shoot regeneration frequency by using HCN explants, while all other combinations also induced shoot formation, albeit with a reduced percentage. Additionally, explant types (HCN, TCN, and WCN) exhibited different responses to different combinations of plant hormones (KT, NAA, and 6-BA), suggesting that, regeneration ability of plant depends on explant type and age [22,61].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively very poor progress has been accomplished on plant regeneration system in legumes [21], due to the unsuccessful in vitro generation tissue culture systems. Several attempts have previously been made to develop successful regeneration system in legumes such as Glycine max [22], Vigna unguiculata [23], Medicago sativa [24], Phaseolus vulgaris [25] Arachis hypogaea [26] Trifolium resupinatum [27], Lathyrus sativus [28], Vigna aconitifolia [29], Onobrychis viciifolia [30], and Stylosanthes humilis [31], Lupinus angustifolius [32], L. luteus [32][33][34], and L. albus [32,35]. Uhde-Stone et al, demonstrated successful transgenic proteoid root development of white lupin by using Agrobacterium rhizogenes [36].…”
Section: Introductionmentioning
confidence: 99%
“…All these influences negatively affect the species growth and practical demand in a large scale. Plant genetic engineering can provide an effective way for genetic improvement (Raza et al 2017). The establishment of genetic transformation system that is a key technique for genetic engineering can be used for plant conservation (Anjusha and Gangaprasad 2016;Chauhan 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In plant tissue culture, the effect of seed viability is not fully researched, especially its role in influencing seed germination, normal seedling development and vigour of seedlings from which cotyledonary explants are derived. Many authors, including Keneda et al [6], Paz et al [7], Shelar et al [8], Hartmann et al [9]and Raza et al [10] have highlighted the difficulties faced during in vitro regeneration of soybean, especially with regard to genotype specificity. These reports, as well as many others, paid less attention to the loss of seed viability, which occurs not only in soybean but even in Galenia pubescens, Swertia chirayita and Zea mays [11][12][13].Therefore, the objective of this research was to determine the effects that seed viability has on germination, seedling vigour and multiple shoot induction.…”
mentioning
confidence: 99%
“…and Raza et al [10] have highlighted the difficulties faced during in vitro regeneration of soybean, especially with regard to genotype specificity. These reports, as well as many others, paid less attention to the loss of seed viability, which occurs not only in soybean but even in Galenia pubescens, Swertia chirayita and Zea mays [11][12][13].…”
mentioning
confidence: 99%